Testing a High Performance, Random Access Priority Queue: A Case Study - McCaffrey, James; Bonar, Adrian (2011 Eighth International Conference on Information Technology: New Generations, 2011)
This paper presents a case study of the functional verification of a custom implementation of a random access priority queue which was optimized for performance. Although data structures have been used for decades few studies have examined the effectiveness of different testing strategies applied to complex data structures. In this study, four different testing approaches were used to test a priority queue. The results showed that a state transition testing approach (13 faults discovered) was clearly superior with regards to the number of faults found than the alternatives of a manual testing approach (3 faults discovered), a unit testing approach (4 faults discovered), and a classical test harness approach (6 faults discovered). Because the state transition testing approach used was in essence a modified form of random input testing, the results of this study suggest that the notion that random input testing is typically less effective than other forms of testing may be an overly broad generalization.